PENGGUNAAN MODEL NUMBER HEAD TOGETHER BERBASIS LESSON STUDY DALAM MENINGKATKAN HASIL BELAJAR KOGNITIF DAN KETERAMPILAN KOLABORASI MAHASISWA - Nosi Qadariah; Titin Mairisiska; Titin Kusayang (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
Education is known as a process of spiritual, intellectual and emotional formation. The implementation of education is realized in the learning process. The learning process in higher education directs students to be able to have good cognitive learning outcomes and collaboration skills. Observation results show that students' cognitive learning outcomes and collaboration skills are low. Therefore, it is necessary to apply a learning model that guides students to be able to have understanding and collaboration skills. One learning design that can overcome problems is the application of the Number Head Together (NHT) model based on Lesson Study (LS). This research is Classroom Action Research (PTK) using the Kemmis and Mc model. Taggart. Planning, action, observation and reflection are the stages of PTK research. Data was analyzed through the percentage of average values ​​and categorized through the level of the Akbar category. The research results showed an increase in cognitive learning outcomes as seen from the posttest scores in cycle I and cycle II with an average score of 77.75 in the good category and 87.5 in the very good category. Students' collaboration skills increased in each indicator from cycle I to cycle II with an average score of 76.75 in the good category and 87.15 which was included in the very good criteria. Therefore, exposure to the LS-based NHT model can improve students' cognitive learning outcomes and collaboration skills.